Combining surface plasmonic and light extraction enhancement on InGaN quantum-well light-emitters. Issue 36 (30th August 2016) - Fadil, Ahmed; Ou, Yiyu; Iida, Daisuke; Kamiyama, Satoshi; Petersen, Paul Michael; Ou, Haiyan
Abstract : Surface plasmon coupling with light-emitters and surface nano-patterning have widely been used separately to improve low efficiency InGaN light-emitting diodes. We propose a design that merges the advantages of both approaches. Abstract : Surface plasmon coupling with light-emitters and surface nano-patterning have widely been used separately to improve low efficiency InGaN light-emitting diodes. We demonstrate a method where dielectric nano-patterning and Ag nanoparticles (NPs) are combined to provide both light extraction and internal quantum efficiency enhancement for InGaN/GaN quantum-well light-emitters. By fabricating dielectric nano-rod pattern on the GaN surface, an optical coating that improves the light extraction is obtained, and furthermore has a low refractive index which blue-shifts the plasmonic resonance of Ag NPs towards the emission wavelength. We investigate emission components from both the GaN and sapphire surface of the semiconductor crystal and show that Ag NPs on dielectric nano-pattern compared to a planar surface, result in a stronger enhancement.